Pattern of body mass index among women with pelvic organ prolapse - Isikhuemen ME; Ekwedigwe KC; Eliboh MO; Sunday-Adeoye I (Ibom Medical Journal, 2018)
BACKGROUND: Overweight and obesity are usually regarded as risk factors for pelvic organ prolapse. This may not be the case in Sub-Saharan Africa where there is chronic malnutrition, physical stress and underweight. OBJECTIVE: To determine the pattern of body mass index in women with pelvic organ prolapse. METHODS: This was a retrospective study which involved the review of medical records of patients between June 2012 and May 2016. Data of 917 women who presented for management of pelvic organ prolapse met the inclusion criteria. Ethical clearance for the study was obtained from Research and Ethics committee of the National Obstetric Fistula Centre, Abakaliki. RESULTS: The mean age was 49.46±13.2 years. The mean weight was 52.04±11.96 kg. The mean body mass index was 21.37±4.73kg/m2. Two hundred and thirty four (25.5%) were underweight and 540 (58.9%) had normal weight. Overall, 15.7% of the study population had obesity and overweight. In women that had first degree uterovaginal prolapse, 20% had obesity and overweight. For women that had second and third degree uterovaginal prolapse, obesity and overweight occurred in 17.7% and 10.6% respectively. CONCLUSION: Most women with pelvic organ prolapse in our setting tend to have normal body mass index or are underweight. Increasing severity of prolapse does not appear to correspond with increasing body mass index in our setting.